2023
DOI: 10.3390/ijms24044174
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Molecular Characteristics, and Evolution of YABBY Gene Family in Melastoma dodecandrum

Abstract: The YABBY gene family plays an important role in plant growth and development, such as response to abiotic stress and lateral organ development. YABBY TFs are well studied in numerous plant species, but no study has performed a genome-wide investigation of the YABBY gene family in Melastoma dodecandrum. Therefore, a genome-wide comparative analysis of the YABBY gene family was performed to study their sequence structures, cis-acting elements, phylogenetics, expression, chromosome locations, collinearity analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
(110 reference statements)
0
3
0
Order By: Relevance
“…This was further supported by their promoter analysis, in which many stress-response elements were revealed, such as MYB, MYC, STRE, ARE, LTR, and W-box (Figure 4D). Same or similar cis-regulatory elements were also discovered in the YABBY genes from other species [68,72,74], suggesting that these YABBY genes have a conserved function in stress response; however, the underlying molecular mechanism remains elusive. Therefore, the determination of the YABBY downstream targets or interactors in the stress response pathway could help improve the defensive traits in quinoa and other crops.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This was further supported by their promoter analysis, in which many stress-response elements were revealed, such as MYB, MYC, STRE, ARE, LTR, and W-box (Figure 4D). Same or similar cis-regulatory elements were also discovered in the YABBY genes from other species [68,72,74], suggesting that these YABBY genes have a conserved function in stress response; however, the underlying molecular mechanism remains elusive. Therefore, the determination of the YABBY downstream targets or interactors in the stress response pathway could help improve the defensive traits in quinoa and other crops.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, expression profile analyses showed that the YABBY genes responded to cold, heat, salt, and drought stresses in stiff brome (Brachypodium distachyon) [68], wheat [39], pak-choi (Brassica rapa ssp. chinensis) [69], common bean (Phaseolus vulgaris) [70], lotus (Nelumbo nucifera) [71], upland cotton (Gossypium hirsutum) [55], twelve stamen Melastoma (Melastoma dodecandrum) [72], and balloon flower (Platycodon grandiflorus) [73]. We assessed the 12 CqYAB genes under salt, drought, and Cd stresses, and found that most CqYAB genes were upregulated under salt and drought stresses but were downregulated under Cd stress.…”
Section: Discussionmentioning
confidence: 99%
“…Melastoma dodecandrum Lour. is a creeping shrub widely distributed across southern China [7][8][9]. A pioneer species is a type of plant, fungus, or organism that is among the first to colonize or inhabit a newly formed or disturbed habitat [10].…”
Section: Introductionmentioning
confidence: 99%